Legal-Political Paradigm of Indonesian Constitutional Court: Defending a Principled Instrumentalist Court - Mirza Satria Buana (Constitutional Review, 2020)
The establishment of the Indonesian Constitutional Court in 2003 signified the formation of a bridge between the judiciary and politics. Through its judicial review process, there is a more tangible presence of the judiciary and court in the political arena. The Court helps with addressing moral predicaments and influencing the products of the legislature. This paper discusses the shifting of the legal-politico paradigm, particularly relating to judicial leadership of the Court because this significantly affects the role of the Court in the political arena. The history of the establishment of the Court’s authority in judicial review is explored through a stylised analysis of the actions of two early Chief Justices. This paper also examines two Court decisions which illustrated the Court’s authority on judicial review because they demonstrated the importance of policy-driven decisions and judicial restraint. The main argument of this work is that it is hard to categorize the legal-politico actions of the Indonesian Court into either legalism or instrumentalism. Often, the Court synthesises the two. The legal-politico paradigm is a dynamic one. The most feasible model of the Indonesian Constitutional Court is that of a Principled Instrumentalist Court, where policy decisions guide the formation of legislation according to constitutional values, but the judges maintain prudential self-restraint.